Um interpretador e typechecker para uma linguagem reversível com pattern-matching simétrico e controle quântico - Zancanaro, Eric Tomás (2018)
Aiming to overcome the theoretical limits imposed by the energetic cost of the classic computational model, new computing paradigms have been formalized. While reversible computing aims to reconcile the reversibility of the physical models with the irreversible way of modelling computations, quantum computing looks to harness the microscopical properties of matter to increase performance. The theoretical development is coupled with the formalization of programming languages that embed those properties independently of their physical implementation. This decoupling allows the simulation of programs belonging to these paradigms by the creation of interpreters. This dissertation presents the implementation of an interpreter and typechecker for a reversible language with quantum control. The project was implemented in the Haskell functional language, allowing for the typechecking and inefficient simulation of quantum sistems, being capable of both forwards and backwards execution. The text also presents the adaptation and execution of algorithms that showcase the embedding of quantum control in the functional language chosen as basis of this work.